Effects of customer brand perceptions on store image and purchase intention: An application in apparel clothing - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Purchase intention for apparel products in retail stores has taken attention in the last decades since the sector has been growing rapidly. The aim of this study is to investigate the efffects of price image, brand image and perceived risk on store image and purchase intention of consumers in apparel sector. The study also examines the metiating effect of store image on the relationship. The data was gathered through questionnaire distributed in face to face interviews. The findings of the research which was conducted on 146 retailer shoppers supported direct effect of price image, brand image and perceived risk on purchase intention. There has been also empirical evidence regarding mediating effect of store image on the relationship between price image and risk perception and purchase intention. (C) 2015 Published by Elsevier Ltd.
Keywords: Apparel; brand image; risk perception; price image; store image; purchase intention; CONSUMERS PERCEPTIONS; RELATIONSHIP QUALITY; PRICE; FAIRNESS; RETAIL